Literature Review: Development of Antiretroviral Therapy in Hiv/Aids Treatment - Amir, Nur Ainun; Hamzah, Pratiwi Nasir; Nur, Muhammad Jabal (Newinera Publisher, 2025)
Human Immunodeficiency Virus (HIV) is a virus that attacks the human immune system. The United Nations Joint Program for HIV/AIDS (UNAIDS) in 2019, stated that the largest HIV-infected population in the world is on the African continent (25.7 million), then in Southeast Asia (3.8 million), and in the Americas (3.5 million). HIV/AIDS symptoms consist of 4 stages, namely stage 1, this phase is referred to as asymptomatic HIV infection where the initial HIV symptoms are still not felt. The goal of antiretroviral therapy (ARV) is to increase the number of CD4+ in T cells, reduce viral load, so that it is expected to reduce mortality. Recommendations for ARV administration are always evolving. Currently, ARVs are given to patients with PLWHA at any clinical stage and CD4+ count. This study aims to determine the development of Antiretroviral therapy (ARV) in the treatment of HIV/AIDS. The method used was literature review with narrative review design to identify and summarise previously published articles on the development of Antiretroviral (ARV) therapy in the treatment of HIV/AIDS. From the 10 articles summarised, it was found that there was an influence of the development of Antiretroviral (ARV) therapy in the treatment of HIV/AIDS over time.